The Prevalence of Anemia Among Children Aged 1-15 Admitted to Hospital in Sivas - Barbaros Şahin Karagün; Özlem Korkmaz; Alper Hazım Gürsu; Ömer Cevit; Soner Solmaz; Bünyamin Bayram; Evrim Aslan; Enver Sancakdar; Ruhiye Cevit; Fikret Özkan; İbrahim Ethem Özsoy (Güncel Pediatri)
Introduction: In this study, we aimed to determine the incidence of anemia in children between the ages of 1-15. Materials and Methods: A total of 14449 patients admitted to pediatric outpatient clinic between 01.01.2012 and 31.12.2012 were retrospectively reviewed from hospital records. Patients between the ages of 1-15 without chronic disease were included into the study in order to evaluate the prevalence of anemia. Results: Of patients admitted to hospital, 8747 were male (60.5%) and 5707 were female (39.5%). Patients were divided into five groups according to age groups including, 2531 patients in 1-3 age group (17.5%), 2872 patients in 4-6 age group (19.9%), 2735 patients in 7-9 age group (18.9%), 2637 patiens in 10-12 age group (18.3%) and 3674 patients in 13-15 age group (25.4%). Anemia was detected in 853 (5.9%) patients, and 465 of them were male (54.5%) and 388 of them were female (45.5%). The distrubition of anemia according to age group was as follows: 205 patients in 1-3 age group (8.1%), 97 in 4-6 age group (3.4%), 98 in 7-9 age group (3.6%), 128 in 10-12 age group (4.9%) and 325 in 13-15 age group (8.9%). The distribution of low MCV values according to age groups was as follows: 1-3 age group; 9.4% (237), 4-6 age group; 5.3% (151), 7-9 age group; 3.8% (104), 10-12 age group; 4.5% (119), 13-15 age group; 8.0% (294). Conclusions: Anemia is one of the most common diseases in the pediatric age group. Anemia continues to be a major health problem in childhood in spite of the policies of the health in our country. Diagnosis and treatment is easy. Physicians should be alert to anemia in childhood and families should be informed about this topic. Also all society must work to improve this situation which affects the health and mental development.